Thrombotic Risk Determined by Protein C Receptor (PROCR) Variants among Middle-Aged and Older Adults: A Population-Based Cohort Study - Manderstedt, Eric; Halldén, Christer; Lind-Halldén, Christina; Elf, Johan; Svensson, Peter J.; Engström, Gunnar; Melander, Olle; Baras, Aris; Lotta, Luca A; Zöller, Bengt; for the Regeneron Genetics Center (Thrombosis and Haemostasis, 2022)
Background The protein C (PC) anticoagulant system has a key role in maintaining hemostatic balance. One missense (Ser219Gly) variant in the PC receptor (PROCR) was associated with venous thromboembolism (VTE) in genome-wide association studies.Objectives This study aimed to determine the thrombotic risk of rare and common PROCR variants in a large population-based cohort of middle-aged and older adults.Methods The exonic sequence of PROCR was analyzed for the Ser219Gly variant and other qualifying variants in 28,794 subjects (born 1923–1950, 60% women) without previous VTE, who participated in the Malmö Diet and Cancer study (1991–1996). Incidence of VTE was followed up until 2018. Qualifying variants were defined as loss-of-function or nonbenign (PolyPhen-2) missense variants with minor allele frequencies (MAFs) <0.1%.Results Re-sequencing identified 36 PROCR variants in the study population (26,210 non-VTE exomes and 2,584 VTE exomes), 11 synonymous, 22 missense, and three loss-of-function variants. Kaplan–Meier analysis of the known Ser219Gly variant (rs867186) showed that homozygosity for this variant increased the risk of disease, whereas heterozygosity showed no effect. Cox multivariate regression analysis revealed an adjusted hazard ratio (HR) of 1.5 (95% confidence interval [CI]: 1.1–2.0). Fifteen rare variants were classified as qualifying and were included in collapsing analysis (burden test and SKAT-O). They did not contribute to risk. However, a Arg113Cys missense variant (rs146420040; MAF = 0.004) showed an increased VTE risk (HR = 1.3; 95% CI: 1.0–1.9).Conclusion Homozygosity for the Ser219Gly variant and a previously identified functional PROCR variant (Arg113Cys) was associated with VTE. Other variants did not contribute to VTE.
Keywords: genetics; PROCR; protein C receptor; venous thromboembolism